Platelets directly regulate DNA damage and division of Staphylococcus aureus. Issue 7 (7th February 2018) - Xu, Jinmei; Yi, Jing; Zhang, Huijie; Feng, Fan; Gu, Shunli; Weng, Lihong; Zhang, Jing; Chen, Yaozhen; An, Ning; Liu, Zheng; An, Qunxing; Yin, Wen; et al.
Abstract : Platelets (PLTs) are classically used in the clinical setting to maintain hemostasis. Recent evidence supports important roles for PLTs in host inflammatory and immune responses, and PLT‐rich plasma has been demonstrated to inhibit the growth of bacteria in vitro and in vivo; however, few studies have examined whether PLTs can inhibit bacterial growth directly, and related mechanisms have not been elucidated further. Accordingly, in this study, we evaluated the effects of PLTs on bacterial growth. We washed and purified PLTs from peripheral blood, then confirmed that PLTs significantly inhibited the growth of Staphylococcus aureus when cocultured in vitro. Moreover, PLTs damaged DNA and blocked cell division in S. aureus. During coculture, PLT‐derived TGF‐β1 was dramatically down‐regulated compared with that in PLT culture alone, and the addition of TGF‐β1tothe coculture system promoted the inhibition of PLTs on S. aureus. Analysis of a murine S. aureus infection model demonstrated that the depletion of PLTs exacerbated the severity of infection, whereas the transfusion of PLTs alleviated this infection. Our observations demonstrate that PLTs could directly inhibit the growth of S. aureus by damaging DNA and blockage cell division, and that PLT‐derived TGF‐β1 may play an important role in this machinery.—Xu, J., Yi, J., Zhang, H., Feng, F., Gu, S., Weng, L., Zhang, J., Chen, Y., An, N., Liu, Z., An, Q., Yin, W., Hu, X. Platelets directly regulate DNA damage and division of Staphylococcus aureus . FASEB J. 32, 3707–3716 (2018). www.fasebj.org